Purine but Not Pyrimidine De Novo Nucleotide Biosynthesis Inhibitors Strongly Enhance the Antiviral Effect of Corresponding Nucleobases Against Dengue Virus - Laurent F. Bonnac; Christine D. Dreis; Madhu Rai; Robert J. Geraghty (Molecules)
Every year, dengue virus affects hundreds of millions of individuals worldwide. To date, there is no specific medication to treat dengue virus infections. Nucleobases, the base of a nucleoside without ribose, are understudied as potential treatments for viral infections. Antiviral nucleobases are converted in infected cells to their corresponding nucleoside triphosphate active form. Importantly, the conversion of nucleobases to their active nucleotide form and their antiviral effect can be enhanced when combined with de novo nucleotide biosynthesis inhibitors. In this work, we evaluated seven purine and pyrimidine nucleobases alone or combined with six purine or pyrimidine de novo nucleotide biosynthesis inhibitors, including novel prodrugs. Our study revealed that while a strong potentiation of purine nucleobases by purine de novo nucleotide biosynthesis inhibitors was observed, the pyrimidine nucleobases were not potentiated by pyrimidine de novo nucleotide biosynthesis inhibitors, possibly highlighting a significant difference between the modulation of purine versus pyrimidine de novo pathways and their impact on nucleobase potentiation. Most significant antiviral effects and potentiation were observed for Favipiravir, T-1105, and ribavirin nucleobases combined with purine nucleotide de novo synthesis inhibitors. These results are significant because drug combinations may solve the limited efficacy observed for some antiviral nucleobase drugs such as Favipiravir.